Thermal management of hydrogen storage in metal reactor by using a corrugated cooling channel with ternary nanofluid - Selimefendigil, Fatih; Senol, Gurel; Öztop, Hakan Fehmi (Elsevier, 2025)
Enhancing the effectiveness of hydrogen storage in metal hydrides requires an efficient cooling system and innovative thermal management strategies. The current study uses a corrugated cooling channel with ternary nanofluid to present an innovative thermal management strategy for metal hydride-hydrogen storage. Using a finite element approach, numerical simulations are carried out for Reynolds numbers (Re) ranging from 2.5 to 100. For both base fluid and nanofluid employed as the coolant in the cooling channel of storage system, the effects of varying corrugation amplitude and wave number on performance are investigated. Considering the lowest and higher Re configurations, heat transfer enhancement factors become 4.6 and 4.2 for base fluid and nanofluid cases. However, varying amplitude and wave number lead to 32%, and 9.8% improvement in the cooling performance of the channel when used with nanofluid. Dynamics of the bed temperature and hydrogen content in the metal hydride are affected most by varying flow Re, and fluid type while corrugation amplitude is effective when used with higher Re. Due to the enhanced cooling process, the storage system maintains approximately 33% of improvement with the highest concentration by using a higher nanofluid velocity. When adopting corrugated channels, both base fluid and nanofluid exhibit better storage performance at t = 300. In comparison to the flat case, the corrugated channel case shows a 12% increase in storage. Even with a flat channel configuration, the absorbed hydrogen concentration of the metal-hydride bed reaches its maximum for nanofluid at t = 1000 s. The results of the current study can be used to develop alternative cooling systems and optimize efficient cooling solutions for hydrogen storage in metal hydrides.
Keywords: Hydrogen storage; Metal hydride; FEM; Ternary nanofluid; Corrugated channel